Comparative advantages of wine in function of territorial marketing strategy - Nadica Jovanovska Boshkovska (Journal of Contemporary Economic and Business Issues, 2018)
economic cohesion and diversity, whose main purpose is to proclaim priority values for the society that need to be realized. Well-conceived and implemented territorial marketing strategy is the basis for sustainable regional development that resolves in well-being of the actors who live on that territory, economic growth and development of the region, recognisability and interest by non-residents of the territory. In order to present directions for establishing a system for promoting territorial attractiveness and the specifics it offers, a set of methodological tools has been applied in the paper to determine whether the comparative advantage of the country is really directed toward the production of wine or there is a need for change in the strategic approach according to the needs and requirements of the international market. Comparative analysis is presented through quantitative assessment using the Balassa index, while the inductive analysis determines the directions and recommendations for a territorial marketing strategy. Based on the calculated results, several directions for potential marketing affirmation are presented, as well as redesigning or directing the recognition of the territory to the service sector in combination with the agricultural specifics that it possesses. The goal is to raise the potential of the service sector through the activation of potentials in the domain of propulsive ICT service that can shape the future profile of the territory in the direction of products with increased added value.
Keywords: M3; Q13; O52; O18; 330; territorial marketing; wine production; comparative advantages; marketing affirmation; recognisability